The new edge in knowledge : how knowledge management is changing the way we do business - O'Dell, Carla S.; Hubert, Cindy (Hoboken, NJ : Wiley, 2011)
"The best thinking and actions in the fast-moving arena of collaboration and knowledge management The New Edge in Knowledge captures the most practical and innovative practices to ensure organizations have the knowledge they need in the future and, more importantly, the ability to connect the dots and use knowledge to succeed today. Build or retrofit your organization for new ways of working and collaboration by using knowledge management. Adapt to today's most popular ways to collaborate such as social networking. Overcome organization silos, knowledge hoarding and "not invented here" resistance. Take advantage of emerging technologies and mobile devices to build networks and share knowledge. Identify what can be learned from Facebook, Twitter, Google and Amazon to make firms and people smarter, stronger and faster. Straightforward and easy-to-follow, this is the resource you'll turn to again and again to get-and stay-in the know. Plus, the book is filled with real-world examples - the case studies and snapshots of how best practice companies are achieving success with knowledge management."--
Includes bibliographical references and index.
Keywords: Knowledge management; Organizational learning; Information resources management; Organizational effectiveness; BUSINESS & ECONOMICS / Decision-Making & Problem Solving